Translation Strategies for Cultural Terms in Mandarin Language in the Subtitles of the Film 'Aftershock' - Putri, Megawati; Nurochman, Nurochman; Hukmawati, Hukmawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Literary works are a medium used by authors to convey ideas and concepts. Literature usually takes the form of a socially-oriented work, such as films. Films are creations that narrate the social or cultural life of a society. This research aims to determine the classification and translation strategies of cultural terms in the film "Aftershock." The method used in this research is qualitative descriptive. The approach used in this study is a case study, describing cultural terms and their translation strategies. The object of this research is the film "Aftershock." There are two theories used in this research: Newmark (1988) for cultural terms and Mona Baker (2011) for translation strategies. The data collection technique used is transcription. The results of this research include the classification of cultural term categories and the translation strategies used in translating cultural terms. The most frequently encountered cultural term category is social culture, and the most frequently encountered translation strategy is the use of more general words.